2020
DOI: 10.1007/s42250-020-00202-y
|View full text |Cite
|
Sign up to set email alerts
|

In-Silico Study on Anti-bacteria and Anti-fungal Activities of 3,4-Dihydropyrimidin-2(1H)-One Urea Derivatives

Abstract: The menace caused by fungi amidst human being and in the world at large is colossal. Their increasing rate of causing havoc has drawn the attention of scientist to developing efficient drug-molecules in order to cure these diseases. In this work, sixteen molecular compounds were studied with aim of investigating the non-bonding interaction between the studied compounds and the receptors using the following software Spartan 14 (optimization), Pymol (for treating downloaded protein), Autodock Tool (for locating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The selected descriptors were molecular weight, Log P, hydrogen bond donor, hydrogen bond acceptor and number of rotatable bonds. 6 that the selected compounds obeyed the Lipinski rule of five 37 and this revealed that the studied compounds have the ability to act as drug which therefore showed the potency of H. umbellata seed as anti-cardiovascular diseases.…”
Section: Calculated Descriptorsmentioning
confidence: 74%
“…The selected descriptors were molecular weight, Log P, hydrogen bond donor, hydrogen bond acceptor and number of rotatable bonds. 6 that the selected compounds obeyed the Lipinski rule of five 37 and this revealed that the studied compounds have the ability to act as drug which therefore showed the potency of H. umbellata seed as anti-cardiovascular diseases.…”
Section: Calculated Descriptorsmentioning
confidence: 74%
“…According to a reference study by Semire et al, 2023 [ 59 ], the compound with the lowest binding affinity is considered to possess the best inhibiting capacity. In this case, ciprofloxacin, and nystatin (reference compounds) exhibited greater potency in inhibiting bacterial gyrase (PDB: 3G75 ), Phosphopantetheine Adenylyltransferase (PDB: 6ckw ), and cytochrome P450 14a-sterol demethylase (CYP51) (PDB: 1ea1 ) compared to the selected compounds ( CA3 , CA4 , CA9 , and CA10 ).…”
Section: Resultsmentioning
confidence: 99%